Dynamic modeling and vibration characteristics of multibody system in axial piston pump - Pingting Ying; Hesheng Tang; Lei Chen; Yan Ren; Anil Kumar (Alexandria Engineering Journal, 2023)
The dynamic vibration characteristics of multibody system in axial piston pump is studied based on a lumped parameter model. The model is used to predict the vibration responses of the rotor assembly and the separator assembly based on Runge-Kutta method. The built model is verified by comparing the theoretical frequencies and experimental results. The developed model is used to investigate the effect of operating circumstances and coefficients of stiffness and damping on the amplitude-frequency vibration response and phase trajectory diagram. The results demonstrated that the frequency simulated by the model is similar to that measured by the experiment, and the error is 8.85%. The frequency of the harmonic is related to the excitation force period and the rotational speed of the axial piston pump. Higher harmonic vibration frequencies are integer multiples of the pump rotation frequency and the inherent flow pulsation frequency. The frequency of pistons impulse is twice that of the rotation. The frequency diagram and phase trajectory diagram are affected by various operating conditions as well as stiffness and damping factors.